Testicular Fibrosis, A Setback of Chemotherapy and Ameliorating Role of Ascorbic Acid - Aisha Abdul Haq, Sadia Iqbal, Uzma Hameed, Aisha Hassan Brohi, Amna Mughal, Dureshawar Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Statement of Problem: The struggle for surviving cancer individuals who have undergone chemotherapy is still a dilemma. Chemotherapeutic agent, Doxorubicin (DOX), causing testicular damage, has been a concern of oncologists for many years. As DOX causes oxidative damage on non-tumorous tissues by the foundation of free radicals, the challenges of protection with various antioxidant therapies have been attempted. The foremost objective was to reduce the cytotoxic properties of DOX to healthy cells. Vitamin C, a water-soluble vitamin, based on its antioxidant property, was applied to study its potential protection to the testicular tissues after oxidative damage by DOX. Objectives: To demonstrate fibrotic changes in the interstitium of testes generated by anthracycline DOX on the mice and designed to study the morphometric changes in DOX affected testes with co-administration of antioxidant Vitamin C. Methodolgy: An Experimental study using male mice were separated into 3 groups (A, B & C). A was treated with normal saline 1 ml intraperitoneal (IP), B was given DOX alone (0.003 mg in 0.03ml /gm body weight IP for 3 doses on 6th, 8th and 10th day of study) and DOX (0.003 mg in 0.03ml /gm body weight IP for 3 doses on 6th, 8th and 10th day of study) + Vitamin C (0.5 mg in 0.01ml/gm body weight per orum daily) was delivered to group C. Animals were sacrificed on completion and organs were kept in Bouin’s fluid and later processing and staining of the tissue was done. Result: Statistical analysis was performed, using ANOVA test to evaluate the significance of parameter among three groups. Widening of interstitium with significant interstitial fibrosis and intra tubular empty spaces were evident as compared to controls. However, co-administration of Vitamin C with DOX significantly reduced (P < 0.001) fibrosis indicating protective role of Vitamin C against DOX induced testicular damage. Conclusion: Experimental study suggested that the antioxidant Vitamin C has a potential role in improving the parameter damaged by DOX. Keywords: Doxorubicin, Vitamin C, Mice, Antioxidant, Oxidative damage, Interstitial, Fibrosis